2-naphthylamine toxicity - Ewelina Czubacka; Sławomir Czerczak (Nofer Institute of Occupational Medicine, 2020)
In the past, 2-naphthylamine (2-NA) was used for the production of azo dyes, as an antioxidant in the cable industry and in the rubber industry. Despite the fact that 2-NA is not produced on an industrial scale, it is still used in small quantities as a model bladder carcinogen in laboratories, and also for sewage control, water analysis and oxytocinase assays. In addition, it is detected in the air in coke ovens, where it is formed as one of the pyrolysis products. The main aim of this work is to provide an actual literature review for health risk assessments related to 2-NA which is still used in laboratories. Occupational exposure to 2-NA is important for the respiratory tract, mucous membranes and the skin, and, to a lesser extent, for absorption from the gastrointestinal tract. It is absorbed into the body through the skin and by inhalation, and then undergoes metabolic changes. Most of the absorbed 2-NA dose is excreted in the urine, in the form of metabolites, metabolites conjugated to acids, and even in an unchanged form. Based on literature data, the effects of 2-NA toxicity in sub-chronic and chronic exposure include contact dermatitis, chronic cystitis and bladder cancer. The authors have concluded that it is recommended to determine the occupational exposure limit which will allow preparing the exposure assessment of people at work. Med Pr. 2020;71(2):205-20